The Historical Evolution of the Administrative Procedure (Comparative Approach) - Luk’yanets, Dmytro M.; Markova, Olena O. (International Journal of Criminology and Sociology, 2021)
The author is engaged in a comprehensive, comparative study of the administrative procedure in Ukraine. In our country, there is no mechanism for the functioning of this institution for a number of objective and subjective reasons, which complicates the study. In this regard, the author refers to the doctrinal legislative and historical experience of such countries as the USA and European countries (Germany, France), since these countries have a fundamental and centuries-old history of the process of formation, development and modernization of the administrative procedure at different historical stages. The history creates law. The purpose of the work is to review the evolution of the administrative procedure and identify key historical and political events that triggered the mechanism of the administrative procedure in the above countries. The result of historical and legal research are the doctrinal concepts of scientists, which influenced the further formation and development of the administrative procedure. During the study, the author received unique knowledge that will be helpful not only in expanding the horizons of scientific knowledge, but also applying them during the writing a doctoral dissertation, which will be the first research work of this level in Ukraine.